Noninvasive detection of lung cancer using exhaled breath. (20th November 2013) - Fu, Xiao‐An; Li, Mingxiao; Knipp, Ralph J.; Nantz, Michael H.; Bousamra, Michael
Abstract: Early detection of lung cancer is a key factor for increasing the survival rates of lung cancer patients. The analysis of exhaled breath is promising as a noninvasive diagnostic tool for diagnosis of lung cancer. We demonstrate the quantitative analysis of carbonyl volatile organic compounds (VOCs) and identification of lung cancer VOC markers in exhaled breath using unique silicon microreactor technology. The microreactor consists of thousands of micropillars coated with an ammonium aminooxy salt for capture of carbonyl VOCs in exhaled breath by means of oximation reactions. Captured aminooxy‐VOC adducts are analyzed by nanoelectrospray Fourier transform‐ion cyclotron resonance (FT‐ICR) mass spectrometry (MS). The concentrations of 2‐butanone, 2‐hydroxyacetaldehyde, 3‐hydroxy‐2‐butanone, and 4‐hydroxyhexenal (4‐HHE) in the exhaled breath of lung cancer patients ( n = 97) were significantly higher than in the exhaled breath of healthy smoker and nonsmoker controls ( n = 88) and patients with benign pulmonary nodules ( n = 32). The concentration of 2‐butanone in exhaled breath of patients ( n = 51) with stages II though IV non–small cell lung cancer (NSCLC) was significantly higher than in exhaled breath of patients with stage I ( n = 34). The carbonyl VOC profile in exhaled breath determined using this new silicon microreactor technology provides for the noninvasive detection of lung cancer. Abstract : We used microreactor to capture all carbonyl compounds in exhaled breath and analyzed captured compounds by Fourier transform‐ion cyclotron resonance mass spectrometry (FT‐ICR‐MS). We have identified four biomarkers for lung cancer diagnosis.